Analysis of The Application of Qirā'ah Mubādalah as A Method of Interpretation of Gender Hadith: Study of the Thoughts of Faqihuddin Abdul Kodir - Zakiyah, Ulfah; Ghifari, Muhammad (Islamic Studies Journal, 2023)
This article discusses the application of Qirā'ah Mubādalah as a gender-based method of interpreting hadith, by examining the thought of Faqihuddin Abdul Kodir. Qirā'ah Mubādalah is a method that invites readers to understand hadith by using a reciprocal perspective that places men and women as equal subjects. This method aims to find a more just and humanistic meaning of hadith, especially in terms of the relationship between men and women. This research uses a type of library research with a descriptive analysis approach. Data were collected by using primary and secondary data sources. Then, the collected data were analyzed critically and interpretively to understand Faqihuddin Abdul Kodir's view on the application of Qirā'ah Mubādalah in gender hadith interpretation. The results of this study show that Qirā'ah Mubādalah developed by Faqihuddin Abdul Kodir has several advantages and disadvantages. The advantage is that this method can provide a new perspective in understanding gender-oriented hadith, namely by reconstructing texts that are specific for men into texts that are relevant for women. The disadvantage is that this method still requires further development on the way of working and its application, because this method cannot be used on hadiths that do not have a clear sentence structure, such as subject, object and predicate.